Non-additivity of subjective expectations over different time intervals - Peter Haan; Chen Sun; Uwe Sunde; Georg Weizsäcker (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We examine the additivity of stock-market expectations over different time intervals. When asked about a ten-year interval, survey respondents expect a stock-price change that is not equal to, but closer to zero than, the sum of their expectations over two shorter time intervals that cover the same ten years. Such sub-additivity is irrational in that it cannot stem from aggregating short-term expectations. Model estimates show that the pattern is consistent with a time perception where shorter time intervals have a proportionally larger weight. We also find that the respondents' degree of additivity is correlated with making larger financial investments.
Keywords: D01; D14; D84; D9; 330; Expectation Formation; Time perception; Sub-additivity; Super-additivity